A STUDY ON ANCYLOSTOMIASIS PREVALENT AMONG 3 RURAL SETTINGS IN ELURU (WEST GODAVARI DISTRICT, A. P.) - R. INDIRA; V. VIVEKA VARDHANI (The Bioscan, 2011)
In this study area Ancylostoma duodenale infection prevailed in adults and children during summer, rainy and winter seasons. In Yanadigudem, females of 10-19 years age group was found as high risk age group in winter. In Vangayagudem, different age groups like 0-4, 5-9 and 10-19, 20-29, 40-49, 50-59, >60 years showed lowest and highest prevalence of ancylostomiasis respectively. In Philhousepet, 32.5% of male children and 25% of men and 30.5% of women showed helminthic infection in rainy season. Much variation is seen in the prevalence of ancylostomiasis in rainy and winter seasons in all the age groups. The infected individuals were treated with Albendazole just after rainy season. Three weeks after antihelminthic treatment, the infection rate among them was lowered; health education also plays a role in reducing the % of infection.